I-spy - Topping, Jenno; Thomas, Betty, 1949-; Kassar, Mario, 1951-; Vajna, Andy, 1944-; Wibberley, Marianne; Wibberley, Cormac; Scherick, Jay.; Ronn, David; Murphy, Eddie, 1961-; Wilson, Owen, 1968-; Janssen, Famke, 1964-; McDowell, Malcolm, 1943-; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2003)
Alex is a federal intelligence agent who has been assigned to find a weapon which has gone missing: a stealth fighter jet which can turn invisible to the human eye. Alex learns a rogue agent has sold the jet to a powerful and unscrupulous underground arms dealer. It seems Gundars is a rabid boxing fan, so in order to get inside his organization, Scott recruits a longtime middleweight champion whose ego nearly exceeds his talent in the ring. The two personalities are like oil and water, and matters are hardly helped by the efforts of less-than-helpful fellow agents Rachael and Carlos.
Originally produced as a motion picture in 2002.
Special features: widescreen and full screen presentations; filmmaker's commentary; four exclusive featurettes.
Director of photography, Oliver Wood ; editor, Peter Teschner ; music, Richard Gibbs ; costume designer, Ruth Carter ; production designer, Maria Hinds-Johnson.
Eddie Murphy, Owen Wilson, Framke Janssen, Malcolm McDowell, Gary Cole, Phill Lewis.
MPAA rating: PG-13; for action violence, some sexual content and language.
Also issued on VHS.
Keywords: Intelligence officers -- Drama; Boxing -- Drama; Films for the hearing impaired; Feature films; Comedy films